Minimum Service Package for the integration of female genital schistosomiasis into sexual and reproductive health and rights interventions - Pillay, Leora N.; Umbelino-Walker, Isis; Schlosser, Delphine; Kalume, Christine; Karuga, Robinson (Frontiers in Tropical Diseases, 2024)
IntroductionFemale genital schistosomiasis (FGS) is a manifestation of infection with schistosomes in the female genital area that affects an estimated 56 million women and girls in Africa. If untreated, FGS can result in severe sexual and reproductive health (SRH) complications. However, FGS is largely unrecognized by SRH providers, and there is no programmatic guidance for the integration of FGS and sexual and reproductive health and rights (SRHR) interventions in the way of a Minimum Service Package (MSP). Therefore, as part of a larger implementation study, an MSP was developed to guide program staff and health planners on how to integrate FGS and SRHR interventions in schistosomiasis-endemic countries.Materials and methodsIn collaboration with 35 experts from six sectors related to FGS, we conducted virtual workshops, engaging the participants within various specialties from around the world to identify a foundational framework for the MSP, as well as the integration points and activities for FGS and SRHR interventions. Several drafts of the MSP were developed, reviewed in virtual workshops, peer-reviewed, and then finalized by the participants.ResultsA participatory and consultative process led to the identification of a foundational framework for the integration of FGS and SRHR interventions, as well as the integration points and activities. This included identifying cadres of staff who would be needed to implement the MSP and the settings in which the service provision would take place.DiscussionDefining an MSP to guide the integration of a minimum package of FGS services in SRHR interventions is a critical step toward ensuring the prevention, screening, diagnosis, and treatment of women and girls in Africa. The MSP can now be rolled out and tested in a country context to start reducing the burden of this preventable and treatable neglected disease.